HUBUNGAN FREKUENSI, JENIS DAN PORSI MAKAN DENGAN KEJADIAN GASTRITIS PADA REMAJA - Mutmainah Handayani; Tigor Abdurrahman Thomy (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Gastritis occurs in people who have an irregular diet and eat foods that stimulate stomach acid production. Prevalence The WHO gastritis incidence rate (2009) in several regions in Indonesia is quite high with a prevalence of 274,396 cases of 238,452,952 inhabitants. Based on the identification of the problem above many factors that can affect the incidence of gastritis, but researchers limit the problems to be examined namely the frequency, type and portion of the meal. The purpose of this study was to look at the relationship between eating patterns and the incidence of gastritis in adolescents in Sungai Menang Community Health Center 2017 Type of quantitative research with Cross Sectional study design. the number of 60 respondents taken by the Stratified random sampling method. The data obtained were then performed chi-square statistical test. Univariate analysis results showed 55% of the majority of respondents had gastritis, which had a frequency of poor eating as much as 65%, and there were 76.7% of respondents who consumed irritated food, and 50% of the respondents eat poorly. Bivariate analysis using chi-square test, the results of the analysis there is a relationship between the type of meal and gastritis (P value = 0.023), there is a relationship between diet and gastritis (P value = 0.000), there is no correlation between eating frequency and gastritis (P value = 0.165), and there is no relationship between eating portions and gastritis (P value = 0.436). It is expected that Puskesmas can provide counseling / health promotion by distributing structured and phased educational brochures, which can increase knowledge about controlling and preventing gastritis.